Anti-psoriatic treatment extends beyond the skin: Recovering of high-density lipoprotein function - Marsche, Gunther (Exp Dermatol, 2014)
Epidemiological and clinical studies have shown a consistent association of psoriasis with systemic metabolic disorders including an increased prevalence of diabetes, obesity and cardiovascular disease. Psoriasis is accompanied by systemic inflammation and low levels of high-density lipoprotein (HDL)-cholesterol. Recent studies provided clear evidence that psoriasis affects HDL composition and function. HDL isolated from psoriatic patients showed a significantly impaired capability to mobilize cholesterol from macrophages, a crucial step in reverse cholesterol transport and markedly lower paraoxonase activity, a protein that co-transports with HDL in serum with well-known anti-atherogenic properties. Of particular interest, successful anti-psoriatic therapy significantly improved HDL composition and function independently of serum HDL-cholesterol levels. These novel findings suggest that the conventional approaches of evaluating cardiovascular risk in psoriasis may be in need of refinement. As these data argue for a loss of beneficial activities of HDL in psoriatic patients, altered HDL functionality should be considered when evaluating the lipid status of patients.